Remember that the "x" in f(x)= some expression is a "place holder". f(x)= x^3, f(a)= a^3, f(b)= b^3. Whatever is in the parentheses on the left replaces the x in the formula. If g(x)= x^3, f(g(x))= f(x^3) and, with f(x)= ln(x), that becomes f(g(x))= f(x^3)= ln(x^3).

f(g(x)) means "first do g(x), then apply f to that". "first do g(x)" gives g(x)= ln(x) and, since f(x)= x^3, "apply f to that" means to cube it: (ln(x))^3.

Of course the answer to 22 is f(x)= ln x, g(x)= x^3 so that f(g(x))= f(x^3)= ln(x^3)